Hama dan Penyakit Anakan Pulai Rawa (Alstonia pneumatophora Backer) di Areal Persemaian BPDAS-HL Kahayan: Pests And Diseases of Swamp Puppies (Alstonia pneumatophora Backer) in The Area BPDAS-HL Kahayan Nursery - Hutagaol, Febriani Friscila; Firdara, Eritha Kristiana; Putir, Patricia Erosa (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2024)
This research aims to identify the types of pests and diseases, analyze the frequency of attacks, the intensity of attacks and the level of damage caused by pests and diseases to the swamp saplings (Alstonia pneumatophora Backer) in the BPDAS-HL Kahayan Nursery area. Sampling in the field uses a diagonal pattern and for the middle part uses the method purpose sampling with a total observation sample of 600 offspring. Based on the research results, it was found that the types of pests and diseases that attack the swamp island saplings (Alstonia pneumatophora Backer), namely the type of pest consisting of wood grasshoppers (Avalanche blackhorn), Shrub snails (Bradybaena similaris), Sumpil (Subulina octogenarian), for diseases namely leaf spots caused by the pathogen Phomopsis sp., leaf spots caused by pathogens Colletotrichum gloeosporioides and leaf spots caused by pathogens Colletotrichum sp. The research results showed that the intensity of attacks from pests was 2.76% lower than the intensity of attacks from diseases of 6.67%.